Insights in nodule-inhabiting plant growth promoting bacteria and their ability to stimulate Vicia faba growth. Issue 1 (31st December 2022) - M. Mowafy, Amr; S. Agha, Mona; A. Haroun, Samia; A. Abbas, Mohamed; Elbalkini, Mohamed
ABSTRACT: The knowledge of the root nodule microbiome is still beyond the minimum. This study has been designed to isolate and characterize plant growth promoting bacteria and testing their ability to promote plant growth. In addition to Rhizobium MAP7, four other strains have been isolated from Phaseolus vulgaris nodules, and they have been molecularly identified as Bacillus MAP3, Brevibacillus MAP4, Pseudomonas MAP5, and Pseudomonas MAP8. The obtained strains showed the ability to produce IAA, siderophores, and HCN with different capabilities. A pot experiment was conducted to investigate the effect of the obtained strains on the physical growth parameters of Vicia faba . The inoculation with Rhizobium MAP7 along with Brevibacillus MAP4 and Pseudomonas MAP5 led to four times increase in the number of nodules (57/plant) compared with that of the control in addition to a significant increase in the physical growth parameters . Additionally, different nitrogen fractions increased significantly in response to this inoculum (226 and 206 mg/g dry weight total nitrogen for shoot and root respectively compared with 175 and 92.5 for control plants). The obtained strains in this study showed a good potentiality as plant growth promotors that might be tried with further crops on wider scale.